Nutrition management of intestinal failure: From neonates to the elderly - Hardy, Gil; Ludlow, Emma (World Nutrition Journal, 2024)
Double enterostomies (DES) and necrotising enterocolitis (NEC) are prevalent in neonatal intensive care units (NICU), commonly resulting from surgical removal of diseased intestine. Sarcopenia prevalence is >40% in community dwelling elderly >65 yrs and is associated with poor nutritional status before/after abdominal surgery, with intestinal failure (IF) and high output stoma losses. Parenteral Nutrition (PN) is the standard of care for Type 2 IF patients with DES or enteroatmospheric fistulas (EAF), but risks catheter-related complications, infection, gut and hepatobiliary dysfunction. Chyme reinfusion therapy (CRT) is a recommended distal feeding technique that may minimise these risks.